2021
DOI: 10.52547/j.health.12.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice (KAP) Study of Nurses Working at Meshgin Valiasr Hospital Regarding Hand Hygiene in 2018

Abstract: Background & objectives: Hand Hygiene by health care providers is a key factor in patients' health. The aim of this study was to determine knowledge, attitude and practice (KAP) of nurses working in Valiasr Hospital in Meshginshahr regarding hand hygiene in 2018. Methods: In this cross-sectional study, 100 nurses working in all wards of Valiasr hospital in Meshginshahr in 2018 were selected by census method. Nurses' knowledge, attitude and practice questionnaire about hand hygiene was used for data collection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Operating room technicians and midwives also performed better than other occupations. In the study by Awazah et al (30), no signi cant relationship was found between knowledge and attitude, performance and attitude towards hand hygiene among nurses .There was a positive and signi cant relationship between knowledge and attitude in the study by Adalatdoust et al (28), which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Operating room technicians and midwives also performed better than other occupations. In the study by Awazah et al (30), no signi cant relationship was found between knowledge and attitude, performance and attitude towards hand hygiene among nurses .There was a positive and signi cant relationship between knowledge and attitude in the study by Adalatdoust et al (28), which is consistent with the results of the present study.…”
Section: Discussionsupporting
confidence: 92%